An Analysis of Factors Affecting the Successful Implementation of Educational Policies in Developing Countries - Ohene, Nyankómàgó (Journal of Education Review Provision, 2021)
This research sought to evaluate the variables influencing the successful implementation of educational policies in underdeveloped countries, with a particular emphasis on Ghana. In this study, a quantitative research approach was taken, and data were gathered through the administration of a survey to a sample size of one hundred fifty policymakers and instructors in Ghana. In order to evaluate the data, both descriptive and inferential statistics were utilized. According to the conclusions, there is a favorable correlation between successful implementation and the governmental, economic, social, and societal variables as well as technological factors. The strongest associations were identified for technological and cultural variables, which suggests that expenditures in technological advancement and cultural awareness can have a beneficial effect on the implementation of educational policies. According to the findings of the multiple regression analysis, all of the variables had a substantial favorable impact on the successful implementation of the plan, with the technological elements demonstrating the strongest effect. According to the findings of the research, in order for educational policies to be successfully implemented in developing countries, a holistic strategy that takes into consideration all of the important variables is required. By considering these variables, policymakers in developing countries will be able to improve the efficacy of educational programs and encourage egalitarian access to education. This research provides important insights for policymakers and stakeholders interested in the administration of educational strategies in underdeveloped countries.